POST TRAINING SUPPORT EFFICACY OF ENTREPRENEURSHIP TRAINING INSTITUTES IN KARNATAKA–AN ANALYSIS - Dr.Venkataram Bhat (EPRA International Journal of Economic and Business Review(JEBR), 2023)
Marketing is an important process in meeting out the needs of a target market by exploring, creating and delivering the values Education and training provide suitable ground for economic development and especially the creation of entrepreneurs is the key to growth. Entrepreneurs are the wealth and job creators as well as play a major role in the ecosystem of development. Governments in India have established many such institutions to motivate, train, orient, and develop entrepreneurs. Rural development and self-employment training institutions originated during the 1980s in Karnataka State and the Ministry of Rural Development has replicated the same all over the country under the sponsorship of District lead Banks. These institutes offer training on various entrepreneurial skills and help the trainees to be successful entrepreneurs. The major objective of the study is to measure and suggest the training institutes regarding the post-training follow-up activities performed by the institutes as received by the trainees. The study was conducted in Karnataka State with the responses collected from 356 trained entrepreneurs who have established businesses and operating them at good or moderate levels. The results were analyzed using percentages and found that the majority have not received any support from the institute. It is suggested to make follow-up genuine to get the real outcomes of training received at the institute.